Dialect (Lahjah) and Synonyms (Mutaradifat) in Arabic: Study of Causality - vlatia, Siti Mahrami I; Nadiyyana, Siti; Hasibuan, Nurul Huda; Nasution, Sahkholid (The Future of Education Journal, 2024)
Arabic is a language rich in vocabulary, but if studied there are some vocabulary words that are not from Arabic itself but are often pronounced with different vocabulary words but the meaning is the same. This is related to the Arabic lahjah (dialect) that develops. The purpose of this study is to find out the relationship between dialect (lahjah) and synonymity in Arabic. The method used in compiling the study of this journal discussion is a qualitative method and library research or literature study as a reference. The findings in the study are that the synonymity of Arabic can be caused by differences in times and regional differences. Along with the development of the times and the spread of Arabic throughout the world led to the emergence of new terms that refer to the same meaning in Arabic with different dialects. This is due to the openness of Arabic to other dialects of the language so as to bring up new words that have the same meaning or meaning and are widely used by Arabic users until now without recognizing the difference whether it is Arabic fusha or Amiyah.